2010
DOI: 10.1016/j.juro.2010.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Shock Wave Lithotripsy for Treatment of Pediatric Urolithiasis: 20-Year Experience

Abstract: Shock wave lithotripsy is an effective treatment for renal calculi in children. Renal parenchymal trauma associated with extracorporeal shock wave lithotripsy does not seem to cause long-term alterations in renal function or development of permanent renal scars in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…#37) In four studies on 231 children, renal scans performed after a follow-up of more than 3 months revealed deterioration in renal function in only one kidney. [25][26][27][28] Very few studies have examined the risk of hypertension developing after SWL in children, and appear to rule out this possibility. 25,29 As for ureteroscopic lithotripsy (URSL), one study on single-kidney patients compared URSL with SWL and found no differences in terms of subsequent renal function.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…#37) In four studies on 231 children, renal scans performed after a follow-up of more than 3 months revealed deterioration in renal function in only one kidney. [25][26][27][28] Very few studies have examined the risk of hypertension developing after SWL in children, and appear to rule out this possibility. 25,29 As for ureteroscopic lithotripsy (URSL), one study on single-kidney patients compared URSL with SWL and found no differences in terms of subsequent renal function.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Despite some studies showing no “long-term” effects of ESWL on a child’s risk of developing hypertension, stunting of renal growth, renal scarring, or deterioration of renal function, data in adults is conflicting with one recent study noting that ESWL was associated with a significant increased risk of incident hypertension. 41,4952 One possibility for the lack of an association in children is that these studies often describe “long term” effects after mean follow ups of 6 months to 5 years which may not be long enough to see effects. 5153 Therefore, any significant long term consequences of ESWL on the kidney and systemically may not have had time to manifest.…”
Section: Acute Managementmentioning
confidence: 99%
“…In our study, we observed that children ≤3 years had higher stone clearance rates (100%) than children >3 years (86.6%) and that a significant relationship was found between the need for a third session and age (≤3 vs. >3 years). In the literature, there are also few studies mentioning SWL as a safe and effective treatment modality in toddlers and infants (6,26). Similarly, we demonstrated that SWL is effective and safe in toddlers.…”
Section: Discussionmentioning
confidence: 99%
“…Shock wave lithotripsy (SWL) was presented as a minimally invasive treatment for nephrolithiasis in the early 1980s (1). SWL has recently become a well-established, safe, and efficacious modality for the treatment of renal stones (2) and is now considered a first-line treatment for the minimally invasive management of pediatric stone disease of the upper urinary tract (3)(4)(5)(6). When used as a primary treatment option for upper tract stones, the efficacy of SWL ranges between 68 and 94% (7,8).…”
Section: Introductionmentioning
confidence: 99%